Death In Children’s Literature Against The Background Of Selected Child And Childhood Discourses - Kwaśniewska-Paszta, Sandra Marta (Society Register, 2022)
The author of the article discusses the sensitive topic of the social taboo of death with regard to the process of the child’s education and development, with particular focus on the use of thanatological literature as a factor shaping the child’s personality. The text presents the perception of the death phenomenon by children, and the essence as well as functions of thanatological literature. It also shows the impact of child and childhood discourses on four well-known literary works for children (at the kindergarten and pre-school age), dealing with the discussed topic. The selected research method consists in qualitative analysis of the content. The works have been selected due to their popularity and presence in scientific publications on the topic of death in children’s literature. Analytical categories of the selected literary works include subjective and objective approach to the child and childhood. The first approach is consistent with the perspective of sociology of childhood and the post-colonial theory, as presented in the article, whereas the second approach refers to the mainstream developmental psychology and the colonial theory. Based on the analysis of content values of the four literary works, it can be concluded that respect for the child’s subjectivity and the value of their voice supports development of the youngest, among others, in the aspect of dealing with the sensitive topic of death.